2000
DOI: 10.1021/jf990906s
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Physical Properties of Derivitized Whey Protein Isolate Powders

Abstract: Pregelatinized starch is employed in many food applications due to the instantaneous nature of thickening and stability imparted by modification. Proteins, however, have been excluded as a viscosifying agent due to requisite thermal treatments required to create structure. Whey protein isolate gels were produced while manipulating heating time, pH, and mineral type/content, producing a variety of gel types/networks. Gels were frozen, freeze-dried, and ground into a powder. Once reconstituted in deionized water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 21 publications
2
51
1
2
Order By: Relevance
“…The linearly increasing storage modulus (G') with frequency is indicative of a higher stability of the gel network in the given frequency range. The lower tan δ values obtained in this study (data not shown) during a frequency sweep is indicative of a good gel network (Hudson et al, 2000). good agreement with the study of cod skin gelatin gels by Gilsenan and Ross-Murphy (2000a) which also showed a slight dependence of G' on frequency that became less obvious as the gelatin concentration increased.…”
Section: Effect Of Concentration On Frequency Sweepssupporting
confidence: 90%
“…The linearly increasing storage modulus (G') with frequency is indicative of a higher stability of the gel network in the given frequency range. The lower tan δ values obtained in this study (data not shown) during a frequency sweep is indicative of a good gel network (Hudson et al, 2000). good agreement with the study of cod skin gelatin gels by Gilsenan and Ross-Murphy (2000a) which also showed a slight dependence of G' on frequency that became less obvious as the gelatin concentration increased.…”
Section: Effect Of Concentration On Frequency Sweepssupporting
confidence: 90%
“…Under alkaline condition, the insolubity of WPs increased due to the larger proportion of proteins being polymerized to higher molecular weight molecules and large aggregates, resulting in turbid and particulate type of gel . According to Bowland and Foegeding (1995), Elofsson et al (1997), and Hudson et al (2000), particulate gels are opaque and synerese which generally have lower water holding capacity due to the large inter-particle pores. On the other hand, WPs produced under acidic conditions (pH < 3.5) were reported to form the translucent or fine-stranded type of gel with higher water holding capacity (Hudson et al, 2000;Ikeda & Morris, 2002).…”
Section: Water Holding Capacity Of Selected Twpc Powdersmentioning
confidence: 99%
“…This product was produced by a heat treatment of WPC solution under a mildly alkaline condition during homogenization followed by a drying process. In addition, the development of freeze-dried and spray-dried derivatized WPI and WPC powders were reported by Hudson, Daubert, and Foegeding (2000), and Resch (2004). These derivatized WP powders were produced by acidifying WPI or WPC solutions (12% protein, w/v) to pH 3.35.…”
Section: Introductionmentioning
confidence: 99%
“…Whey and its proteins are also used as food ingredients because of their unique functional characteristics like emulsifying, gelling, thickening, foaming and water binding effects (Kinsella and Whitehead, 1989). As foodstuffs they are applied not only because of their functional properties, but also because of their high nutritive value and GRAS status (Bryant and McClements, 1998;Harper, 2000;Hudson et al, 2000). They are used at optimal levels in foods to improve their texture, flavor and color and to increase the amount of proteins with high biological value (Kilara, 1994).…”
Section: Introductionmentioning
confidence: 99%